Central and peripheral fatigue in knee and elbow extensor muscles after a long‐distance cross‐country ski race. (12th June 2016) - Boccia, G.; Dardanello, D.; Zoppirolli, C.; Bortolan, L.; Cescon, C.; Schneebeli, A.; Vernillo, G.; Schena, F.; Rainoldi, A.; Pellegrini, B.
Abstract : Although elbow extensors (EE) have a great role in cross‐country skiing (XC) propulsion, previous studies on neuromuscular fatigue in long‐distance XC have investigated only knee extensor (KE) muscles. In order to investigate the origin and effects of fatigue induced by long‐distance XC race, 16 well‐trained XC skiers were tested before and after a 56‐km classical technique race. Maximal voluntary isometric contraction (MVC) and rate of force development (RFD) were measured for both KE and EE. Furthermore, electrically evoked double twitch during MVC and at rest were measured. MVC decreased more in KE (−13%) than in EE (−6%, P = 0.016), whereas the peak RFD decreased only in EE (−26%, P = 0.02) but not in KE. The two muscles showed similar decrease in voluntary activation (KE −5.0%, EE −4.8%, P = 0.61) and of double twitch amplitude (KE −5%, EE −6%, P = 0.44). A long‐distance XC race differently affected the neuromuscular function of lower and upper limbs muscles. Specifically, although the strength loss was greater for lower limbs, the capacity to produce force in short time was more affected in the upper limbs. Nevertheless, both KE and EE showed central and peripheral fatigue, suggesting that the origins of the strength impairments were multifactorial for the two muscles.